Deregulation of Bank Entry and Branching: Impact on Competition - Melanie S. Milo (Philippine Institute for Development Studies (PIDS), 2001)
This paper looks at public policy towards bank entry and branching in the Philippines and its impact on the sectors structure, conduct and performance. In particular, it argues that regulatory restrictions on bank entry and branching have had adverse effects on competition, while the liberalization of these restrictions have led to a more competitive banking sector. The paper has two main sections. Section II presents the history of regulation of bank entry and branching in the Philippines. The impact of these regulations on the banking sector is then briefly discussed in Section III by looking at some indicators of changes in financial structure, measures of concentration and operational efficiency. Section IV then presents some policy implications.
Keywords: 330; banking reforms; entry barriers; Bank; Bankenregulierung; Markteintritt; Bankenreform; Philippinen